International trade in waste materials - Johannes Hackmann (Intereconomics, 1994)
The general public views international trade in waste materials overwhelmingly with disfavour. Is this negative attitude justified? Professor Hackmann offers an allocative and an ethical assessment of this question.
Keywords: 330; Environment